Mangiferin mitigates dexamethasone-induced insulin resistance in rats: insight into vascular dysfunction and hepatic steatosis - Alsaedi, Abdullah Q.; Nader, Manar A.; El-Kashef, Dalia H.; Abdelmageed, Marwa E. (Frontiers in Pharmacology, 2025)
AimInsulin resistance (IR) is a hazard to human health in which peripheral insulin-target organs, like the liver, become less sensitive to normal levels of insulin. Dexamethasone (DEX)-induced IR is a distinct model of IR. Hence, the present study investigates the efficacy of mangiferin (Mang) in the reversal of DEX-induced IR in the livers and aortas of rats.Main methodsRats were randomly assigned into six groups: control (CTRL), Mang, DEX, and three pretreated groups (received Mang 25 mg/kg, 50 mg/kg, or 100 mg/kg, orally for 14 days, with DEX (1 mg/kg) injected from day 8 to day 14). On day 15, serum, liver, and aorta tissues were obtained and examined using biochemical, histological, and immunohistochemical assessments.Key findingsMang administration attenuated DEX-induced IR, evidenced by decreased oral glucose tolerance test (OGTT) and fasting serum insulin levels, in addition to improving the DEX-induced hepatic and aortic histopathological alterations. Additionally, Mang attenuated DEX-induced alterations in liver function parameters and improved serum lipid profiles, oxidative stress, and antioxidant biomarkers. Mang also markedly increased hepatic and aortic levels of insulin receptor substrate 1 (IRS1), protein kinase B (AKT), AMP-activated protein kinase (AMPK), and peroxisome proliferator-activated receptor-gamma (PPAR-γ) levels. Mang reduced hepatic and aortic tumor necrosis factor-alpha (TNF-α), forkhead box protein O1 (FOXO-1), hepatic NOD-like receptor family pyrin domain-containing 3 (NLRP3), phosphoenol pyruvate carboxy kinase (PEPCK), and glucose 6-phosphatase (G6Pase). Mang elevated hepatic glycogen synthase kinase3 (GSK3α) and glycogen synthase (GS2) levels. Furthermore, Mang ameliorated aortic expression levels of endothelin-1 (ET-1), vascular cell adhesion molecule-1 (VCAM), c-Jun N-terminal kinase (JNK), nuclear factor kappa B (NF-κB), and vascular endothelial growth factor (VEGF) and increased endothelial nitric oxide synthase (eNOS) and prostacyclin (PGI2) levels.ConclusionMang administration could confer hepato- and vasculo-protective activity via its hypolipidemic, hepatoprotective, anti-inflammatory, and antioxidant efficacy.